Golden prey - Sandford, John, 1944 February 23- (New York : G.P. Putnam's Sons, 2017)
"The man was smart and he didn't mind killing people. Welcome to the big leagues, Davenport. Lucas Davenport's first case as a U.S. Marshal sends him into uncharted territory, in the thrilling new novel in the #1 New York Times-bestselling series. Thanks to some very influential people whose lives he saved, Lucas is no longer working for the Minnesota Bureau of Criminal Apprehension, but for the U.S. Marshals Service, and with unusual scope. He gets to pick his own cases, whatever they are, wherever they lead him. And where they've led him this time is into real trouble. A Biloxi, Mississippi, drug-cartel counting house gets robbed, and suitcases full of cash disappear, leaving behind five bodies, including that of a six-year-old girl. Davenport takes the case, which quickly spirals out of control, as cartel assassins, including a torturer known as the "Queen of home-improvement tools" compete with Davenport to find the Dixie Hicks shooters who knocked over the counting house. Things get ugly real fast, and neither the cartel killers nor the holdup men give a damn about whose lives Davenport might have saved; to them, he's just another large target. Filled with his trademark razor-sharp plotting and some of the best characters in suspense fiction, Golden Prey is further reason why "Sandford has always been at the top of any list of great mystery writers" (The Huffington Post)"--
Keywords: Davenport, Lucas (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; FICTION / Crime; FICTION / Suspense; FICTION / Mystery & Detective / General; Suspense fiction; Mystery fiction